Proposed UPV-Strength Relationship for Concrete Subjected to Sulfate Attack - Latef Khlef, Feras (Anbar Journal of Engineering Sciences, 2012)
The purpose of this paper is to developing a mathematical relationship between the Ultrasonic Pulse Velocity (UPV) and the compressive strength for concrete specimens subjected to different amounts of exposure of sulfate attack. The experimental data were collected from a research work by the author using concrete subjected to sulfate exposure and form a literature used an extensive concrete work without sulfate exposure. The sulfate exposures studied were 0%, 3%, and 6% of fine aggregate. It is found that with the same amount of sulfate exposure a clear relationship curve can be drawn to describe the UPV and compressive strength. This paper proposes the UPV-strength mathematical expression suitable for prediction of the concrete strengths when subjected to sulfate attack.